1997
DOI: 10.1152/ajpgi.1997.272.3.g589
|View full text |Cite
|
Sign up to set email alerts
|

Diminished retinoic acid signaling in hepatic stellate cells in cholestatic liver fibrosis

Abstract: Hepatic stellate cells (HSC) participate in liver fibrogenesis via myofibroblastic activation, the extent of which appears to correlate with the loss of cellular vitamin A. The present study has tested a hypothesis that HSC activation is associated with diminished retinoic acid (RA) signaling. Pure HSC were isolated from rats with cholestatic liver fibrosis induced by bile duct ligation (BDL) and sham-operated animals (Sham). Northern blot analysis of HSC RNA from BDL confirmed fibrogenic activation of the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 0 publications
3
103
1
2
Order By: Relevance
“…This alternative, however, seems unlikely since hepatic stellate cells in vitro rapidly loose their capacity to respond to retinoic acids, which is reflected by decreased retinoic acid and RAR levels (52,53). Here, we show that CRABP-I mRNA levels, after a transient rise between days 0 and 3, were reduced at later time-points.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This alternative, however, seems unlikely since hepatic stellate cells in vitro rapidly loose their capacity to respond to retinoic acids, which is reflected by decreased retinoic acid and RAR levels (52,53). Here, we show that CRABP-I mRNA levels, after a transient rise between days 0 and 3, were reduced at later time-points.…”
Section: Discussionmentioning
confidence: 65%
“…Competition analysis showed that PPAR␤-RXR binding to a consensus DR1-like PPRE was actively competed for binding to the DR2-like RARE of the CRBP-I promoter. In contrast to PPAR␤, the expression of RARs becomes strongly reduced during hepatic stellate cell culturing (52,53). PPAR␤ might thus control the expression of CRBP-I by binding to responsive elements in the CRBP-I promoter.…”
Section: Discussionmentioning
confidence: 97%
“…In this model, we did not detect clear modifications of CRBP-1 expression in lobular HSC. In contrast, Ohata et al (1997), using the same model, have shown that the mRNA expression of CRBP-1 was drastically reduced in isolated HSC. There are no ready explanations for this apparent discrepancy.…”
Section: Crbp-1 Expression In Liver Myofibroblastsmentioning
confidence: 90%
“…Electrophoretic Mobility Gel Shift Assay-HSC nuclear proteins (5-10 g) or PPAR␥, JunD, or RXR␣ in vitro translated using the coupled transcription/translation systems (Promega, Madison, WI) were incubated in a reaction mixture (20 mM HEPES, pH 7.6, 100 mM KCl, 0.2 mM EDTA, 2 mM dithiothreitol, 20% glycerol, 200 g/ml poly(dI-dC)) on ice for 15 min and further incubated with 1-2 ng of ␣-32 P-labeled doubled-stranded ARE-7 (the PPAR response element from the adipocyte fatty acid-binding protein gene) or AP-1 element (26) for an additional 30 min. The reaction mixture was then resolved on a 6% nondenaturing polyacrylamide gel in 4ϫ TBE (45 mM Tris, 45 mM boric acid, 1 mM EDTA).…”
Section: Methodsmentioning
confidence: 99%